Constitutive Features of Deliberate Language Shift: A Case Study of Afghan Immigrants as a Community of Practice - Dr. Zulfiqar Ali (University of Chitral Journal of Linguistics and Literature, 2023)
The study is aimed to determine the constitutive features of deliberate language shift by Afghan immigrants in Chakwal (Punjab, Pakistan). The researchers selected 10 business practitioners living for at least 10 years in the Punjabi community. The semi-structured interviews and non-participants observations were conducted for data collection. The researchers used "Community of Practice" (CofP) as a theoretical framework. CofP Model has three elements that helped the researchers determine the constitutive features of language shift by Afghan immigrants. The researchers found out that the regional displacement left the Afghan immigrants with the least liberty to exercise their language in all the fields of life because the local stakeholders were not conversant with Afghan's language. As a result, they started borrowing words from Punjabi and Urdu languages. The study's findings reflect that the influence of these languages permanently substituted their native language vocabulary with that of Panjabi and Urdu. The researchers noticed that linguistic adaptations are tactically intentional and need-based and not accidental. The market competition is the driving force towards their deliberate language shift. This language shift is determined through practitioners' attitudes and communication attempts to generate more significant revenue and make better fits in the community of practice.